1D metallic edge states of oxygen-terminated zigzag graphene edges. (22nd March 2019) - Li, Y Y; Chen, M X; Weinert, M; Li, L
Abstract: The honeycomb lattice of graphene exhibits a chiral symmetry that guarantees a Dirac point where linearly dispersing bands crosses with zero density of states. Enhanced functionalities such as metallicity and semi-conductivity are predicted by breaking the chiral symmetry in graphene zigzag nanoribbons and the selective chemical functionalization of their edges. Here we synthesize oxygen-terminated zigzag ribbons via Ag catalytic nanoparticle-assisted oxygen etching of epitaxial graphene/SiC(0 0 0 1). Using scanning tunneling microscopy/spectroscopy and density functional calculations, we demonstrate 1D metallic edges in oxygen terminated zigzag edges, due to two sets of states at the Dirac point—localized oxygen-induced states and extended resonances derived from the Dirac states of graphene. The edges states are robust, persisting even after air exposure. These findings indicate that the selective functionalization of graphene edges can be an effective means to tailor its properties.